Managerial rationales for investing and divesting under uncertainty - Rikke S. Platou (Taylor & Francis Group, 2019)
This study examines the strategic investment and divestment decisions of fifteen Norwegian power companies that were made in response to an increasingly uncertain business environment. The objective is to investigate the rationales underlying decisions for strategic renewal through the lens of real options logic. The qualitative analysis of 68 decisions allowed for an in-depth understanding of the multiple considerations top managers of energy companies deliberate prior to making strategic directive decisions. Findings show that uncertainty triggers diversification and that companies tend to move unidirectionally. However, the underlying rationales and determinants for strategic decisions vary considerably among the companies examined in this study—from deliberate, long-sighted strategic visions to opportunistic, short-sighted gut feelings. Further, boards of directors and owners exert some influence on top managers’ strategic decisions to expand their business activities. Knowing that some arguments carry more influence is important for managers who attempt to steer companies through turbulent times successfully.